Effect of Below Knee Prosthesis on Muscle Force Production and Joint Contact Forces of Knee and Hip Joints during Walking in Amputees - M. Kamali; K. Sharif-Moradi; A. Tahmasebi; Kh. Jabal-Ameli (Afarand Scholarly Publishing Institute, 2017)
Aims: Caused by prosthesis, the kinematic and kinetic pattern changes during walking in persons with unilateral lower-limb amputation lead to muscle and joint pains. The aim of the study was to investigate the effects of below-knee prosthesis on the muscle force, as well as the knee and hip contact force, in the persons during walking.  Instrument & Methods: In the quasi-experimental study, eight non-veteran male persons with lower-knee amputation referred to Technical Orthopedic Clinic of Rehabilitation Faculty of Isfahan University of Medical Sciences were studied in 2015. The subjects were selected via available sampling method. The Qualysis motion analysis system was used to measure the walking kinematic variables. Kinematic data was recorded by Qualysis Track Manager 2.7 software and was analyzed by OpenSIM 3 software. Data was analyzed by SPSS 22 software using independent T test. Findings: The healthy stance time percentage and the healthy vibration time percentage were significantly more (p=0.001) and lesser (p=0.04) than the prosthetic side, respectively. The anterior-posterior, vertical, and medial-lateral hip and knee contact forces and the forces of the selected lower limbs, as well as the hip extensor, abductor, and flexor forces and the knee extensor force, at the healthy side were more than the prosthetic side, but insignificantly (p>0.05). Conclusion: The unilateral lower-knee prosthesis increases the healthy weight-bearing time percentage during walking. In addition, the healthy lower-limb joints are overloaded to some extent, which is due to more activities of the lower-limb muscles.